Sweet potato response to biochar application on sub-optimal dry land - Edyson Indawan; Sri Umi Lestari; Nurita Thiasari (Brawijaya University, 2018)
This trial was aimed to evaluate the performance of sweet potato cultivars on biochar application. The treatments were carried out using a Split-plot Design with three replications. The cultivars were placed on main plots and biochar doses were on sub-plots. The thirteen cultivars consisted of seven varieties and six accessions from Tribhuwana Tunggadewi University and Brawijaya University collections. The applied biochar doses were B0 (0 t/ha) and B1 (5 t/ha). The experimental unit measuring of 5 m x 0.6 m consisted of single row and planted with a spacing of 25 cm in row or 20 cuttings/row. The storage root weight, % dry matter, storage root dry weight, dry weight of biomass, harvest index and yield estimation were determined. The results showed that the sweet potato cultivars gave a significant response to the biochar application on fresh storage root weight, storage root dry weight, biomass dry weight, harvest index and storage root yields, but no interaction between cultivars and biochar doses. Storage root yield ranged from 8 to 21 t/ha without biochar and from 10 to 23 t/ha with 5 t biochar /ha, except for Beta 1 and Boko. The use of 5 t biochar /ha increased storage root yields that ranged from 8 to 45%.